2015
DOI: 10.3329/jbcps.v32i4.26062
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Surgical Site Infection by Tuberculosis – A Rising Cause of Concern ?

Abstract: Background: Surgical site infections causes significant morbidity and mortality of patients and causes more difficult to treat if unexpected cause behind the infection like tuberculosis. Delayed surgical site infection after initial healing are uncomfortable for both surgeons and patient.Methods: Wound tissue from 18 patients with delayed surgical site infection not responding to antibiotics used for pyogenic infection were collected and examined histopathologically.Results: Of the 18 patients, 9 revealed hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…SSI by Mycobacterium tuberculosis is uncommon. However, several studies had reported M. tuberculosis associated SSI in patients with no history of tuberculosis (42)(43)(44)(45). This indicated that the virulence of M. tuberculosisis very high.…”
Section: Discussionmentioning
confidence: 99%
“…SSI by Mycobacterium tuberculosis is uncommon. However, several studies had reported M. tuberculosis associated SSI in patients with no history of tuberculosis (42)(43)(44)(45). This indicated that the virulence of M. tuberculosisis very high.…”
Section: Discussionmentioning
confidence: 99%